Digital Transformational Leadership A Village Head On Organizational Citizenship Behavior Through Work Climate And Job Satisfaction Village Officials In Lombok Island - Ahyat, Muhammad; Sahar, Sahar; Afriwan, Okky; Saniah, Eluiz Yansirus; Saputra, Agus Marjan (Jurnal Manajemen Industri dan Logistik, 2022)
The purpose of this study was to determine the effect of the Village Head's Transformational Leadership on Organizational Citizenship Behavior (OCB) through Organizational Climate and Job Satisfaction of Village Officials in East Lombok Regency. The steps used to analyze the data are Confirmatory Factor Analysis, Multiple Regression Analysis and Path Analysis. The results showed that Transformational Leadership has a positive but not significant effect on Job Satisfaction, Transformational Leadership has a positive and significant effect on Work Climate, Transformational Leadership has a positive and significant effect on OCB, Work Climate has a positive and significant effect on OCB, Work Climate has a positive and significant effect on Job Satisfaction. Behavior and Job Satisfaction have a positive and significant influence on Organizational Citizenship Behavior (OCB). has a positive but not significant effect on OCB and job satisfaction has a positive and significant effect on OCB.